Qirati Method: Unlocking Student Motivation and Controversy of Closing Educational Institutions - Imam Tabroni; Muhamad Dika Pransah; Teguh Agus Wahyudi (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The purpose of this research is to increase children's interest in learning the Qur'an at TPA al-Muhajirin. This type of research is qualitative with a grounded theory design. The resource persons in this study were teachers and students. Data collection techniques were intensive and in-depth information search through interviews, observation, and documentation. Analysis by formulating data variations with triangulation. Data interpretation uses the author's arguments through the literature. The results of the study found that the factors causing a decrease in children's interest in learning the Qur'an at TPQ Rumah Tahfizh al-Muhajirin were declining student health and fatigue, lack of support from parents, unpleasant school programs, influential colleagues, divided by IT development, and incompetent teachers. While there is no solution to the factors causing the decline in children's interest in learning the Qur'an at TPQ, because TPQ has stated that in the coming year TPQ will close from various considerations. The recommendation is to increase teacher competence with the qiroati method so that interest in learning the Qur'an can be developed.